2001
DOI: 10.1046/j.1365-2648.2001.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse endoscopists in United Kingdom health care: a survey of prevalence, skills and attitudes

Abstract: Nurse endoscopy is widely practised in the UK and is not limited to one procedure or solely for diagnostic purposes. Benefits include good patient acceptability, improved care and safety. Most clinicians predict an important but restricted role for nurse endoscopy in contributing to endoscopic services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 7 publications
1
36
0
Order By: Relevance
“…2,6,7,11,12 Moreover nurses are more thorough in examining the oesophagus and stomach, and patients expressed more satisfaction immediately following an endoscopy by a nurse. In contrast, there was a trend towards more investigations in the year after the primary endoscopic procedure by a nurse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,6,7,11,12 Moreover nurses are more thorough in examining the oesophagus and stomach, and patients expressed more satisfaction immediately following an endoscopy by a nurse. In contrast, there was a trend towards more investigations in the year after the primary endoscopic procedure by a nurse.…”
Section: Discussionmentioning
confidence: 99%
“…1 This represents a significant increase in numbers when compared with figures from October 2000. 2 A survey in the USA in 1999 revealed that 15% (24 of 164) of units in a gastroenterology fellowship programme use paramedical personnel to perform flexible sigmoidoscopy 3 and this role was approved by state boards of nursing in most states.…”
Section: Recommendations For Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The nurses knowledge for control group at pre and post program was changes, although they are not exposed them to instructional program, It is noticeable at most of program domains and total domains which as 47% of them don't know how to prepare the patients for endoscopy at pre-test and reduces the percent of not known between them to 43.5% at posttest, this finding is supported by Pathmakanthan et al,(2001) they presented in their study on 102 nurse endoscopists to determine the prevalence and potential benefits associated with attitudes towards nurse endoscopy in the UK. The significant advancements shown at the post-guidelines program period indicate these nurses were in real need for such information.…”
Section: Part Ii: Discussion Of Pre-and Post Nurses' Responses For Camentioning
confidence: 74%